Les formes du voyage : cartes et espaces des guides de voyage - Nicolas Verdier (In Situ, 2011)
The relations between maps and guides are old in France. This article questions this relation by being first interested in the nature of maps contained in the guides, then try to put forward the relation existing in the form of the map and the form of the text in the guide. It is mainly through the relation with the maps in bands that the question is developed here. The studied corpus starts at the beginning of the XVIIIth century to end at the end of the XXth century.